2004
DOI: 10.1128/jcm.42.9.4147-4153.2004
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of a Rapid Human Immunodeficiency Virus (HIV) Serial Serologic Testing Algorithm for Diagnosis and Differentiation of HIV Type 1 (HIV-1), HIV-2, and Dual HIV-1-HIV-2 Infections in West African Pregnant Women

Abstract: We evaluated a two-rapid-test serial algorithm using the Determine and Genie II rapid assays, performed on-site in four peripheral laboratories during the French Agence Nationale de Recherches sur le SIDA ( , respectively. The specificities were 98.4% (95% CI, 96.9 to 99.3%) and 100% (95% LL, 99.3%), respectively. All serological assays gave concordant results for infections with single types. By contrast, for samples found to be infected with dual HIV types by the Genie II assay, dual reactivity was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 32 publications
1
57
1
1
Order By: Relevance
“…Different studies have shown that among individuals diagnosed as dually seropositive, often only HIV-1 or HIV-2 DNA is isolated (more often HIV-1), a phenomenon commonly thought to be explained by crossreactivity. 12,[36][37][38][39][40][41] In our study it is therefore possible that dual infection was overestimated, although to what extent is uncertain. Diagnosis of dual infection would ideally require the isolation of both viruses from an individual through the use of PCR techniques.…”
Section: Discussionmentioning
confidence: 77%
“…Different studies have shown that among individuals diagnosed as dually seropositive, often only HIV-1 or HIV-2 DNA is isolated (more often HIV-1), a phenomenon commonly thought to be explained by crossreactivity. 12,[36][37][38][39][40][41] In our study it is therefore possible that dual infection was overestimated, although to what extent is uncertain. Diagnosis of dual infection would ideally require the isolation of both viruses from an individual through the use of PCR techniques.…”
Section: Discussionmentioning
confidence: 77%
“…Of the four rapid assays evaluated, the Genie II HIV1/HIV2 was found to be most accurate for discriminating between HIV-1 and HIV-2 (this finding has not always been confirmed in other settings 9 ) but did misidentify an HIV-2 sample as being HIV-1 which is a problem given the treatment issues around HIV-1 and HIV-2. However, use of the Genie II HIV1/HIV2 in Guinea-Conakry would be particularly compromised by the fact that the test requires sera (instead of whole blood) and is subject to cold chain availability, both of which are important operational considerations at peripheral facilities.…”
Section: Discussionmentioning
confidence: 94%
“…Quantitative real-time RT-PCR was used to amplify a region with low degree of variability in the long terminal repeat (LTR) gene of the HIV-1 genome as previously described. 33 RT-PCR was performed as a one-step assay on 50 ng of RNA run in duplicate, using commercially available TaqMan one-step RT-PCR MasterMix (Applied Biosystems), with an internal standard for quantification. Amplification and data acquisition were performed with the ABI Prism 7000 sequence de-tection system (Applied Biosystems).…”
Section: Viral Rna Quantification By Real-time Quantitative Rt-pcrmentioning
confidence: 99%